The effect of organızatıonal culture & authentıc leadershıp on whıstleblowıng: cross-cultural research between turkey & ethıopıa - Wozır, Fathe Mahdı (My University, 2018)
İfşa etme diğer adıyla düdük çalma, batılı olmayan kültürlerde nadiren incelenen, Etiyopya'da ise hiç incelenmemiş konulardan biridir. ABSTRACT Whistleblowing is one of the rarely studied topics in non-western cultures, and nonein Ethiopia.
Keywords: Ahlaki olmayan davranışların ifşaedilmesi; Authentic Leadership; Ethiopia; Etik; Etiyopya; İşletme; Organizational culture; Otantik liderlik; Örgüt kültürü; Örgütsel davranış; Turkey; Türkiye; Whistleblowing; Yönetim